Preliminary findings of down-regulated genes in nasopharyngeal carcinoma - Sim, Edmund U. H.; Kie-Leong, Alan Toh; Thung-Sing, Tiong (Malaysian Society for Molecular Biology and Biotechnology, 2008)
The cause and mechanism of nasopharyngeal carcinoma (NPC) progression are multifactorial and multigenic in nature. Despite the increasing number of genes found to be linked with NPC, the comprehensive list of associated genetic factors remains incomplete and the precise molecular pathways to this cancer are largely undefined. Here we show early evidence of possible association between several genes and the tumourigenesis of NPC. By employing the GeneFishingTM DEG Technique that allows the comparative analysis of expression profiles between normal and tumour nasopharyngeal biopsy tissues, we have identified 10 differentially expressed genes. These genes were down-regulated in tumours relative to normal control and have never been brought into the context of NPC tumourigenicity. Our findings represent preliminary yet novel clues of several associative genetic factors to neoplastic malignancy of the nasopharynx.